Study of Silica Sinter Mineral Content, Surface Temperature, and Fluid Type of Waya Makawa Hot Spring Ploly Village, Makian Island, North Maluku - Ningrum, Rohima Wahyu; Taib, Suryani; Aswan, Marwis (Lambung Mangkurat University Press, 2024)
ABSTRACT − Waya Makawa hot spring is the only hot spring in Ploly Village, Makian Island, North Maluku. Hot water utilization is still in the form of hot spring tourism and has not been explored further. The surface temperature of the Waya Makawa hot spring is quite high, so it is interesting to research because the temperature is the dominant parameter of geothermal areas. This study aimed to determine the mineral content of sintered silica and its relationship to surface temperature, as well as to determine the type of fluid (hot water) of Waya Makawa. The research method used is a quantitative method with mud samples to determine the content of sintered silica tested using the XRF method. A thermocouple temperature sensor measures The hot water sample for its surface temperature. Water samples were taken using a random sampling method to determine the content of chemical elements from hot springs and then analyzed using trilinear diagrams. The mineral content test results obtained in the Waya Makawa mud sample have a fairly high silica mineral content. Point 1 has a silica mineral content of 54.49%, while at point 2 it is 57.84%. At the location of point 1, the average surface temperature obtained is around 37.6 o C, while at point 2 it is around 40.6 o C. The relationship between surface temperature and mineral content in Waya Makawa hot water is very significant, the higher the temperature, the greater the silica mineral content at that point. The results of the chemical analysis show that the Waya Makawa hot spring is an alkaline chloride fluid type and is immature water, as well as an indication of a high permeable zone (fault). This hot water domination system is located in low relief, has been altered with silica characteristics, has silica sinter reserves, and occurs in many tectonic fault systems.